Peran Teknologi dalam Pembelajaran daring di Masa Pandemi - Umi Handriyani Pasaribu; Reka Hosana Br Ginting; Vany Oktaviana; Sonti Ria Kristiani Manik; Vivintri ON Nabutaek (Arus Jurnal Pendidikan, 2022)
The spread of the COVID-19 virus has had a huge impact on human life, including in the world of education. The government has set a new policy related to the education system in Indonesia, namely learning is done online. So technology is needed to support the online learning process. This research was conducted to determine the effectiveness of using technology in online learning. In the implementation of online learning, technology is needed to help the interactive and creative learning process. There are now many learning platforms such as e-learning, google classroom, moodle, study houses, video conferences and so on.